Comparison of astigmatism between glued and sutured scleral-fixated intraocular lens - Nithya Nair; Vijay Mathur; Pawan G Kumar (Delta Journal of Ophthalmology, 2022)
Background Posterior chamber intraocular lens implantation in the bag is the preferred mode of correcting aphakia. But, in certain circumstances, this is not possible, thereby requiring modalities of secondary fixation of intraocular lens (IOL). Purpose The aim of this study was to compare the postoperative astigmatism till six months after surgery between the sutured scleral-fixated IOL and the glued scleral-fixated IOL. Patients and methods This is a single-center, prospective, observational, open-label study comparing the postoperative outcome (till 6 months), including astigmatism and best-corrected visual acuity (BCVA), of sutured scleral-fixated intraocular lens (SFIOL) (Group 1) and glued SFIOL (Group 2). There were 25 patients in each group. Patients were followed up on day 1, first week, first, second, third, and sixth month postoperatively. During each postoperative visit, slit-lamp biomicroscopy was performed to evaluate the status of the cornea, anterior chamber, IOL, and position of haptics. Uncorrected visual acuity, BCVA, refraction, and keratometry values (corneal astigmatism) were noted. Cylindrical refraction denoted total astigmatism. The IOL astigmatism was derived by subtracting the corneal astigmatism from the total astigmatism. Results The difference in corneal astigmatism between the two groups was statistically significant at 1, 3, and 6 months postoperatively (P=0.004, 0.002, and 0.012, respectively). The final values at 6 months were 3.00±1.68 diopters (D) in the sutured SFIOL group and 2.08±0.56 D in the glued SFIOL group. The glued SFIOL group required less cylindrical correction till 6 months of follow-up. The BCVA, 6 months postoperatively, was 0.36±0.19 in Group 1 compared with 0.32±0.17 in Group 2, with no statistically significant difference (P=0.404). Conclusion Both techniques proved to be good options for the implantation of SFIOL, but glued SFIOL was better as it led to less astigmatism and hence the need for less spectacle correction.